Progress in the Application of Satellite Remote Sensing Technology in Urban Night Light Pollution Monitoring - Wang, Dongyue (Transactions on Environment, Energy and Earth Sciences, 2024)
The satellite remote sensing technology has provided good research conditions for analysing urban light pollution intensity. Many types of satellites are used worldwide to monitor light pollution. This article describes the application progress of satellite remote sensing technology in urban night light pollution monitoring, analyzes their technical characteristics and advantages, and summarizes the important role of satellite remote sensing technology in light pollution monitoring. By summarizing the technical parameters of satellite data, such as spatial resolution, temporal resolution, and spectral range, it shows that remote sensing technology provides long-term and stable data support for global and regional light pollution monitoring, especially for the study of the spatial distribution and changing trends of light pollution, which has unique advantages. This paper analyzes the temporal and spatial distribution of night light brightness in different areas based on specific cases and reveals the relationship between light pollution, urbanization and economic development. Although remote sensing technology has significant advantages in light pollution monitoring, it still faces some challenges during its application, including limited data resolution, insufficient sensitivity to new light sources such as LEDs, and high data acquisition costs. This paper also proposes future research directions, including improving the resolution of sensors, expanding spectral bands, optimizing data processing methods, and combining multi-source remote sensing data and ground measurement data to achieve more accurate light pollution monitoring.